Two dimensional numerical investigations on the velocity profile in a shock tunnel - Diyar I.A.; Al-Falahi A.; Yusoff M.Z.; Shuaib N.H. (EuroJournals, Inc., 2023)
This paper presents a numerical study on the profile of flow velocity inside a short duration high speed flow shock tunnel facility available at UNITEN Malaysia. The current work focuses on the two-dimensional velocity profile inside the shock tunnel to complement an earlier study on one-dimensional velocity profile in the same shock tunnel. The main aim is to investigate on the flow behavior after the primary diaphragm rupture by tracing the velocity profile at selected sections of the high speed flow shock tunnel. A twodimensional time-accurate Euler solver was used to simulate the flow process inside the shock-tunnel and special attention is paid to elucidate the steady flow conditions obtained in the nozzle section after the rupture of the secondary diaphragm. Details of the flow process such as shock wave motion, reflected shock wave and interaction with the contact surface were tailored and the results were depicted in two dimensional graphs and contours. 2010 EuroJournals Publishing, Inc.